2011
DOI: 10.1097/iae.0b013e3181fe54c7
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Atrophy in Retinal Angiomatous Proliferation

Abstract: Geographic atrophy occurs frequently in patients with RAP after treatment. This information, if confirmed in other cohorts, would be valuable for the counseling of patients with this disease and for the understanding of the pathogenesis of this condition and its progression after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 25 publications
4
45
0
1
Order By: Relevance
“…Even though this was not observed in our cohort, 27 eyes (34.2%) presented with some degree of GA at baseline, and this number rose to 47 at the last visit (59.5%). McBain et al [28] reported GA development in 53% (n = 35) of RAP eyes, independently of the treatment chosen (IV anti-VEGF and/or PDT), a result that supports our findings. The aforementioned CATT research group paper [27] also focused on the risk factors for the development of GA and found that the RAP subtype of AMD accounted for a 1.69-fold risk of GA development.…”
Section: Discussionsupporting
confidence: 82%
“…Even though this was not observed in our cohort, 27 eyes (34.2%) presented with some degree of GA at baseline, and this number rose to 47 at the last visit (59.5%). McBain et al [28] reported GA development in 53% (n = 35) of RAP eyes, independently of the treatment chosen (IV anti-VEGF and/or PDT), a result that supports our findings. The aforementioned CATT research group paper [27] also focused on the risk factors for the development of GA and found that the RAP subtype of AMD accounted for a 1.69-fold risk of GA development.…”
Section: Discussionsupporting
confidence: 82%
“…31,32 In the present study, 17.7% (11 of 62) of eyes exhibited type 3 NV. Retinal angiomatous proliferation has been reported to follow a more aggressive natural course than type 1 or 2 NV, despite the excellent response to anti-VEGF therapy with a dramatic reduction in CMT and intraretinal edema.…”
Section: Discussionmentioning
confidence: 92%
“…Retinal angiomatous proliferation has been reported to follow a more aggressive natural course than type 1 or 2 NV, despite the excellent response to anti-VEGF therapy with a dramatic reduction in CMT and intraretinal edema. 32,33 The occurrence of high rates of RPE atrophy at presentation and the development of new atrophy or geographic atrophy during follow-up have also been described. 32,34 Intriguingly, the WIF-1 level was by far the highest in patients with type 3 NV in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Also, RAP is highly associated with geographic atrophy. 9 Therefore, we believe that the anti-VEGF agent, which has a minimum effect on the choroid, is better to be used for the treatment of RAP. Atul Kumar: Diagnosis is based on clinical presentation described above, and further confirmed on OCT. One of the major differentials for AOFVD is Best's macular dystrophy.…”
Section: Hidetaka Matsumotomentioning
confidence: 99%